NORMATIVE DATA FOR THE FUNCTIONAL MOVEMENT SCREEN™ IN MALE GAELIC FIELD SPORTS. Issue 7 (11th March 2014) - Fox, D; O'Malley, E; Blake, C
Abstract : Background: Hurling and Gaelic Football are amateur team field sports which are native to Ireland. Due to the speed, player to player contact and multidirectional nature of the sports, injury to players is inevitable. Objective: Determine normative values for the Functional Movement Screen™ (FMS) in Elite and Sub-Elite male Gaelic Football and Hurling players. Design: A cross sectional study of functional movement in Gaelic games. Players were video recorded completing the FMS™ and scored post-test. Setting: Testing of Elite and Sub-Elite Gaelic players in a gym and university biomechanics laboratory. Participants: A total of 62 players (injury-free) were included. This consisted of 41 Hurling, and 21 Gaelic Football players. 30 of these participants were deemed Elite and 32 were deemed Sub-Elite. The mean age of the sample was 22.15±3.02 years. Risk factor assessment: The FMS™ is a screening method which is proposed to identify potential injury causing deficits in the human body. There are 7 specific components to the test (Deep Squat, Hurdle Step, In-line Lunge, Shoulder Mobility, Active Straight Leg Raise, Trunk Stability Push Up, Rotary Stability), accompanied by 3 clearing tests (Spinal flexion, Spinal extension, Shoulder internal rotation with flexion). Each is scored out of 3 for a maximum of 21. The clearing tests are not scored. Main outcome measurement: Functional Movement Screen™ (FMS). Results: The FMS mean score for the sample was 15.56±1.456. The Elite group (15.8±1.58) scored higher than the Sub-Elite group (15.34±1.31), but there was no significant difference between groups. Conclusions: This study provides normative reference values for Gaelic Players. Elite Gaelic Players perform no better than a young, active population in the FMS indicating a potential problem with the FMS as a measure. The ability of the FMS to detect injury risk is not well supported and clinicians should be cautious using it as such.